MEMBERIKAN KEJELASAN BANTUAN HUKUM BAGI MASYARAKAT KECIL (AWAM) DEMI KEADILAN - Ruloff Fabian Yohanis Waas (SOCIETAS, 2015)
ABSTRACT Legal aid institutions or aid advocates as the legal defenses in legal aid programs for the underprivileged were always expected to defend the legal interests of the underprivileged, eventhough the Supreme Court of the Republic of Indonesia through the Directorate General for the General Courts only provide limited funding. The research method was qualitative using the obtained data directly from the sample and the population through in depth interviews. The data analysis technique was descriptive which is intended to obtain clear and good overview, and able to provide detailed data as possible related to the research object. Result of the study shows that judicially formal, legal aid activities in the general sense means that the activities of legal services to every person who lodged the case is included as a part of the positive law in Indonesia. It can be seen in Act No. 14 of 1970 about the Supreme Court and Article 254 HIR that is set on the right to obtain legal services for every person who lodged the case whether he/she is rich or poor